Perceived Organizational Support and Organizational Commitment Among Nurses: Examining The Mediating Role of Job Satisfaction - Nainggolan, Delfitri Aulina; Hasanuddin, Hasanuddin; Hardjo, Suryani (Psikoborneo: Jurnal Ilmiah Psikologi, 2026)
The study was motivated by the low level of organizational support and recognition perceived by nurses, which affected their job satisfaction and organizational commitment. This study aims to examine the effect of perceived organizational support on organizational commitment with job satisfaction as a mediating variable among nurses. This research used an explanatory quantitative approach with purposive sampling techniques based on the criteria of nurses with PNS, PPPK, and BLUD status who had worked for more than one year. The subjects consisted of 157 nurses at Dr. Ferdinand Lumban Tobing General Hospital, Sibolga, North Sumatra. Data were collected using the Perceived Organizational Support Scale, Organizational Commitment Questionnaire (OCQ), and Job Satisfaction Survey (JSS). Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) through SmartPLS 4. The results showed that perceived organizational support had a positive and significant effect on organizational commitment and job satisfaction. Job satisfaction also had a positive and significant effect on organizational commitment and mediated the relationship between perceived organizational support and organizational commitment. The research model explained 72.1% of the variance in organizational commitment. These findings highlight the importance of organizational support, fairness, and recognition in improving nurses’ satisfaction and organizational commitment.Penelitian dilatarbelakangi oleh rendahnya dukungan dan pengakuan organisasi yang dirasakan perawat, sehingga berdampak pada menurunnya kepuasan kerja dan komitmen organisasi. Penelitian ini bertujuan menganalisis pengaruh perceived organizational support terhadap komitmen organisasi dengan kepuasan kerja sebagai variabel mediator pada perawat. Penelitian menggunakan pendekatan kuantitatif eksplanatif dengan teknik purposive sampling berdasarkan kriteria perawat berstatus PNS, PPPK, dan BLUD serta memiliki masa kerja di atas 1 tahun. Subjek penelitian berjumlah 157 perawat di RSU Dr. Ferdinand Lumban Tobing, Sibolga, Sumatera Utara. Pengumpulan data dilakukan menggunakan Skala Perceived Organizational Support (16 item), Organizational Commitment Questionnaire (OCQ) 24 item, dan Job Satisfaction Survey (JSS) 36 item. Analisis data menggunakan Structural Equation Modeling (SEM) berbasis Partial Least Squares (PLS) melalui SmartPLS 4. Hasil penelitian menunjukkan bahwa perceived organizational support berpengaruh positif dan signifikan terhadap komitmen organisasi (β = 0,835) dan kepuasan kerja (β = 0,882). Kepuasan kerja juga berpengaruh positif dan signifikan terhadap komitmen organisasi (β = 0,322) serta kepuasan kerja memediasi pengaruh perceived organizational support terhadap komitmen organisasi (β = 0,284). Model penelitian mampu menjelaskan 72,1% variasi komitmen organisasi. Temuan ini menegaskan pentingnya dukungan, keadilan, dan penghargaan organisasi untuk meningkatkan kepuasan dan komitmen organisasi perawat.